IABP and cardiogenic shock: A heartbreaking story - Bendjelid, Karim (The American heart journal, 2018)
Recently, however, the appropriateness of intra-aortic balloon pump (IABP) counterpulsation in patients with cardiogenic shock (CS) has been the subject of significant debate.3,4 Indeed, an adequately powered, randomized trial of IABP in patients with CS secondary to myocardial infarction (IABP-SHOCK II) has demonstrated neither a survival benefit for IABP support in comparison with the control, nor any benefit with respect to secondary outcomes.3,4 For this reason, IABP has been downgraded in current American and European guidelines.5-7 In the current issue, Hsu and colleagues from the John Hopkins Hospital retrospectively studied 74 patients who underwent IABP insertion for CS related to non-ischemic heart failure.8 The authors demonstrated that even non-AMI patients requiring IABP received a hemodynamic advantage from this technique; nearly 30% of patients died under hemodynamic assistance or required advanced cardiovascular support.8 Moreover, when evaluating the 28-day outcome, a history of ischemic cardiomyopathy (ICM) and a low baseline left ventricular cardiac power index (LVCPI <0.28 W/m2) at the time of the IABP implantation were the most powerful predictors of a poor 28-day outcome (P=.005).8 The authors should be commended for this effort to investigate the predictors of IABP failure in patients with CS related to non-primary ischemic heart failure, as the majority of the literature is focused on AMI patients.[...]a threshold value of LVCPI as a significant predictor of a poor outcome is intuitive as the LVCPI encompasses the three major components of cardiac reserve: preload, contractility and heart rate.9 Indeed, in the face of impaired contractility, the heart is highly dependent on chronotropic competence to maintain adequate circulation.10 As noted by the authors,8 patients who suffered adverse events had higher mean heart rates than patients who did not suffer adverse events, a condition that may have reduced the efficiency of IABP.11 Hsu and colleagues have also demonstrated the significance of the right ventricular cardiac power index as a predictor of a poorer outcome using a univariable logistic regression.Interestingly, in the IABP-SHOCK II trial, baseline C-reactive protein levels were significantly higher in the IABP group than in the control group.4 Thus, particularly poor performance of IABP at this stage of an accompanying vasoplegic shock can be easily explained as demonstrated in patients with CS related to AMI.15 The IABP-SHOCK II randomized controlled trial, published in an authoritative journal, appears to be in unconditional disagreement with those who have advocated the use of IABP for the beneficial treatment of “coronary shock”.4 However, the pathophysiology of CS related to AMI is complex, as this disease is characterized by a profound depression of myocardial contractility, resulting in a vicious spiral of reduced cardiac output, low blood pressure, and systemic inflammation leading to vasodilatation and the perpetuation of cardiogenic shock.16,17 From our current understanding of the mechanisms operating during CS, we may speculate that IABP cannot by itself correct all the derangements of this complex condition.18 Is it possible that for CS and IABP management, evidence-based medicine (EBM) lacks a sound scientific basis19? EBM rests on the assumption that questions in clinical medicine can be formalized or reduced into statistical questions.